EFEKTIVITAS TEKNOLOGI M-BIO PADA PENGELOLAAN LIMBAH PADAT INDUSTRI PENYAMAKAN KULIT SUKAREGANG GARUT 2) 1) UNTUK PERTANIAN RAMAH LINGKUNGAN - Rudi Priyadi; Rakhmat Iskandar; Rina Nuryati; Yoni Hermawan (Bumi Lestari Journal of Environment, 2014)
The objective of the research was to find out the effectiveness of M-Bio technology on themanagement of solidwaste of tanneryindustry inSukaregang Garutforsustainable agricultureand to obtain the treatmentthat givesthe best results of the  waste management of solid wasteof tanneryindustryinSukaregangGarut into organic fertilizer.The research was conductedin theLaboratory ofthe Faculty ofAgriculture, UniversityofSiliwangiTasikmalayain3 stages.Stage-1was the contact time of M-Bio inthesolid waste with a dose of15ml/L24hours: 48hours: 72 hours: 96 hoursand120 hours, and thecheck(without treatment ofM-Bio). Theparametertested was the Crcontent.Stage-2was thecontinuationof thestage-1, toobservethe decreased levels ofCr+6, i.e.withtheincreasingdoses ofM-Bio to 20ml/Lwiththe contacts timeof 10, 15, and20days. The parametersobserved werethe content ofCr, N, P, K, andpH.Stage-3 was thefurthertesttoobtainthe besttreatmenttoproduceorganic fertilizer.Thetreatmentwasthe contact times 5, 10, 15 dayswith the doseof M-Bio 8.5;17;25.5;and34ml/L;so there were12treatmentcombinations. The parameterstested wereCr+6, total Cr, N,P,K, andpH.The results showedthatthe best treatmentcombinations toreduceCr+6were thetreatmentcombinationF(contact time 10days+dose of17ml/LM-Bio) andJ(contact time 15days+doseof17ml/LM-Bio) whichgivesthe lowestCr6+6+(from 1.21 to 2.56 mg/kg), andgave aquitehighcontentof nitrogen (N) (2.35 to 2.45%), and thecontent ofPhosphorous(P) andPotassium(K)below 0.1mg/kgandbelow0.5mg/kg, andthe pHwas4.55–5.05.It was concludedthat theM-Bio was effectiveandcouldreducetheharmfulCr, so thesolidwasteof tanning industryin Sukaregangcouldbeusedasorganicfertilizerforsustainableagriculture.